Book Reviews (The Australian journal of anthropology, 1972)
Book reviewed in this article: The Destruction of Aboriginal Society. Outcasts in White Australia. The Remote Aborigines. By C. D. Rowley Chariots of the Gods? By Erich von Daniken Archaeology of the Gallus Site, Koonalda Cave. Edited by R. V. S. Wright Fighting with Food. Leadership, values and social control in a Massim society. By Michael W. Young One Father, One Blood. Descent and Group Structure Among the Melpa People. By Andrew Strathern Crocodile and Cassowary: Religious Art of the Upper Sepik River, New Guinea. By Douglas Newton Papua New Guinea. Prospero's Other Island. Edited by Peter Hastings The Human Aviary. A Pictorial Discovery of New Guinea. By George Holton and Kenneth E. Read A Revised Linguistic Survey of Australia. Edited by W. J. Oates and Lynette F. Oates Notes on the Bandjalang Dialect Spoken at Coraki and Bungawalbin Creek, N.S.W. By Nils M. Holmer Papers on the Languages of Australian Aboriginals. Contributions by B. J. Blake A Partial Vocabulary of the Ngalooma Aboriginal Tribe. By Harold Aubrey Hall Dating Techniques for the Archaeologist. Edited by Henry N. Michael and Elizabeth K. Ralph The Aborigine Today. Edited by B. Leach. Paul Hamlyn